Exploring cultural beliefs and practices associated with weaning of children aged 0-12 months by mothers attending services at Maternal Child Health Clinic Kalisizo Hospital, Uganda - Nandagire, Wakabi Hellen; Atuhaire, Catherine; Egeineh, Ambirigen Teclar; Nkfusai, Claude Ngwayu; Tsoka-Gwegweni, Joyce Mahlako; Cumber, Samuel Nambile (The Pan African Medical Journal, 2019)
Introduction: despite the fact that mothers know the exact age to wean their infants, majority of the mothers do not practice exclusive breastfeeding due to cultural beliefs and practices. The purpose of the study was to explore cultural beliefs and practi ces associated with weaning children at the Maternal Child Health Clinic Kalisizo Hospital. Methods: this was a simple qualitative study. Seven in-depth-interviews were conducted among 7 mothers of children within the ages 0-12 months attending post-natal care services using self-generated semi-structured key informant's guide. This took place at the Maternal Child Health Clinic Kalisizo Hospital. Purposive sampling method was used to select mothers for the study. Three themes were generated namely: identification of the different cultural beliefs and practices associated with weaning, how the different cultural beliefs are practiced and the impacts of these cultural beliefs and practices. Data were analysed using thematic analysis. Results: although a majority of the mothers knew the recommended age to wean their infants, they did not ignore the ill-informed cultural beliefs, taboos and practices from their elders such as peer pressure, advice and counselling from mother-in laws and teachings from older women who are seen as role models. Conclusion: adherence to cultural beliefs, taboos and practices, have a powerful influence on weaning, hence hindering exclusive breast feeding
Keywords: Cross-sectional; Qualitative; Cultural beliefs; Practices; weaning; Children